PERANAN PENTING PENGELOLAAN PENYERAPAN KARBON DALAM TANAH - Harris Herman Siringoringo (Jurnal Analisis Kebijakan Kehutanan, 2014)
This paper represents a review of managing carbon sequestration in soils derived from various sources and aims to provide scientific information and policy inputs to decision makers in agriculture and forestry sectors. The study was focused on soil carbon sequestration and functions; factors which influence soil carbon levels; how much carbon can be stored; and land management options for carbon sequestration. Soil carbon sequestration will stimulate important changes in land management and has a significant effect on soil properties, and agriculture and forest land quality. Increasing soil organic carbon (SOC) stocks through the increase of inputs and/or decreasing C decomposition is the heart of SOC sequestration.